2018
DOI: 10.3390/ph11020047
|View full text |Cite
|
Sign up to set email alerts
|

High Concentrations of Sodium Chloride Improve Microbicidal Activity of Ibuprofen against Common Cystic Fibrosis Pathogens

Abstract: Ibuprofen (IBU-H), a widely used anti-inflammatory, also shows a marked antimicrobial effect against several bacterial species, including those involved in cystic fibrosis such as Pseudomona aeruginosa, methicillin resistant Staphylococcus aureus and Burkholderia cepacia complex. Additionally, our results show significant synergy between water soluble Na-ibuprofen (IBU-Na) and ionic strength. Salt concentrations above 0.5 M modify the zeta potential promoting the action of Na-IBU; thus, with 1 M sodium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
(26 reference statements)
1
17
0
1
Order By: Relevance
“…As mentioned above, there are evidences of benefits attributed to the inhalation of a hypertonic saline solution (HTS) in the treatment of patients with lung diseases. It has even been described beneficial effects on the bactericidal activity of ibuprofen against agents involved in the development of lung pathologies (Muñoz et al, 2018 ). Thus, we performed MD simulations to evaluate the influence of ionic strength (NaCl concentration) on the structure of the Ibuprofen–Mpro complexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, there are evidences of benefits attributed to the inhalation of a hypertonic saline solution (HTS) in the treatment of patients with lung diseases. It has even been described beneficial effects on the bactericidal activity of ibuprofen against agents involved in the development of lung pathologies (Muñoz et al, 2018 ). Thus, we performed MD simulations to evaluate the influence of ionic strength (NaCl concentration) on the structure of the Ibuprofen–Mpro complexes.…”
Section: Methodsmentioning
confidence: 99%
“…One example is Ibuprofen, a nonsteroidal anti-inflammatory drug (NSAID) widely used for relief of pain, fever and inflammation, which has demonstrated novel pharmacological actions against bacteria (Dai et al, 2019 ; Obad et al, 2015 ; Shah et al, 2018 ), fungi (Ogundeji et al, 2016 ; Sanyal et al, 1993 ) and viruses (Pan et al, 2018 ; Veljkovic et al, 2015 ). Interestingly, a short time ago, it was reported a nebulizable formulation of sodium Ibuprofen in high ionic strength with bactericidal properties for the treatment of respiratory infections of fibrotic patients (Muñoz et al, 2018 ). In addition to exhibiting antiviral properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the pH signifies the effect of ibuprofen on L. monocytogenes and E. coli O157:H7. A recent study declared an enhanced effect of ibuprofen accompanied by sodium chloride (Muñoz et al 2018). Another study confirmed the anti-biofilm effect of ibuprofen against E. coli (Baldiris et al 2016).…”
Section: Discussionmentioning
confidence: 93%
“…We have previously reported that sodium-ibuprofenate is a membrane penetrating amphiphatic molecule with antibacterial properties in the presence of hypertonic saline, rendering the combination bactericidal for Pseudomonas aeruginosa and Burkholderia cepacia (21).…”
Section: Introductionmentioning
confidence: 99%